FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WIRAUSAHA PADA MAHASISWA WIDYATAMA - Wijaya, Ni Putu Nurwita Pratami; Ramadhan, Nabilah (BISMA: Jurnal Bisnis dan Manajemen, 2019)
Entrepreneurship has an important role in reducing the unemployment numbers in many countries, especially Indonesia. The synergy of three sectors, consisting of government as regulator, educational institution as educator, and private sector as capital provider, is significant in the process of creating and educating young entrepreneurs. University as one of the educational institutions has a strategic role in educating prospective entrepreneurs. However, many university graduates are still facing the dilemma of choosing to work in a company or being an entrepreneur and starting their own business. Therefore, this study examines the factors that influence student entrepreneurial intention. The sample of this study consisted of 100 respondents who were the students of the Faculty of Business and Management, Widyatama University, Bandung. Data were analyzed using multiple regression. The results showed that the factors influenced student entrepreneurial intention were university support (26.3%) and proactive personality (26.9%). Keywords : Entrepreneurial intention, university support, proactive personality